2009
DOI: 10.1111/j.1574-6941.2009.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Viruses in subarctic lakes and their impact on benthic and pelagic bacteria

Abstract: Virus-bacterium interactions were investigated in the pelagic and benthic habitats in a set of lakes along an altitudinal gradient in the subarctic northern Sweden. Viral and bacterial abundances showed a significant variation between the lakes, with the highest benthic microbial abundances recorded in a high-altitude lake [993 m above sea level (a.s.l.)], whereas the highest pelagic microbial abundances were found in a low-altitude lake (270 m a.s.l.). In the pelagic habitat, there was also a distinct differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…These direct observations by TEM were never reported from marine and freshwater sediments Filippini et al, 2006;Säwströ m et al, 2009). This contrasts with viral infection rates inferred from indirect approaches where viral production is often calculated from changes in viral abundances before and after incubations (for example, dilution approach), primarily in contemporaneous marine sediments (Hewson and Fuhrman, 2003;Glud and Middelboe, 2004;Mei and Danovaro, 2004;Danovaro et al, 2008b;Corinaldesi et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These direct observations by TEM were never reported from marine and freshwater sediments Filippini et al, 2006;Säwströ m et al, 2009). This contrasts with viral infection rates inferred from indirect approaches where viral production is often calculated from changes in viral abundances before and after incubations (for example, dilution approach), primarily in contemporaneous marine sediments (Hewson and Fuhrman, 2003;Glud and Middelboe, 2004;Mei and Danovaro, 2004;Danovaro et al, 2008b;Corinaldesi et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the dilution or viral decay assays indicate that viruses could control a large part of microbial activities in the sediments (Mei and Danovaro, 2004;Danovaro et al, 2008b;Corinaldesi et al, 2010). However, only small numbers of visibly infected cells have been observed in both freshwater Filippini et al, 2006;Säwströ m et al, 2009) and marine benthic environments (Danovaro et al, 2008b). These results have led to the concept of 'infectivity paradox' in which high viral abundance contrasts with low number of visibly infected prokaryotes in sediments Filippini et al, 2006;Danovaro et al, 2008a).…”
Section: Introductionmentioning
confidence: 91%
“…Low numbers of infected bacteria may hint that viruses do not proliferate in some marine benthic sediments . It is possible that the viruses may have been deposited from the water column and that the sediment bacteria are not their host (Säwström et al, 2009).…”
Section: Viruses In Microbial Mats and Biofilmsmentioning
confidence: 99%
“…By using stable carbon (delta C-13) and nitrogen (delta N-15) isotopes, it was found that benthic algae support zooplankton growth during winter in a shallow, clear subarctic lake (Karlsson and Sawström, 2009). Whole-lake estimates of carbon flux through algae and bacteria in benthic and pelagic habitats of clear-water lakes in subarctic northern Sweden suggest that productivity in these lakes is largely determined by benthic autotrophic production and metabolism of allochthonous organic carbon (Ask et al, 2009). In Water Environment Research, Volume 82, Number 10-Copyright © 2010 Water Environment Federation 1908 addition, it was found that phytobenthos and phytoplankton pigment strategies differ which implies divergent responses to environmental change between the phytobenthos and phytoplankton in high latitude lakes (Bonilla et al, 2009).…”
Section: Monitoring Seasonal Variation In Species Composition Of Thementioning
confidence: 99%